Evaluating the effects of a peer-led suturing and wound management workshop for doctors working in a psychiatric hospital. (9th July 2018) - Buick, T. A.; Hamilton, D.; Weatherdon, G.; O'Shea, C. I.; McAlpine, G.
Abstract : Background: Psychiatric in-patients are often transferred to an emergency department for care of minor wounds, incurring significant distress to the patient and cost to the service. Aims: To improve superficial wound management in psychiatric in-patients and reduce transfers to the emergency department. Method: Thirty-four trainees attended two peer-led suturing and wound management teaching sessions, and a suturing kit box was compiled and stored at the Royal Edinburgh Hospital. Teaching was evaluated using Kirkpatrick's model, and patient transfer numbers were acquired by reviewing in-patient Datix reports and emergency department case notes for 6 months before and after teaching. Results: The proportion of patients transferred to the emergency department decreased significantly from 90% 6 months before the workshop to 30% 6 months after ( P < 0.05). Trainees engaged positively and there was a significant increase in self-confidence rating following the workshop ( P < 0.05). The estimated cost saving per transfer was £183.76. Conclusion: The combination of a peer-led workshop and on-site suturing kit box was effective in reducing transfers to the emergency department and provided a substantial cost saving. Declaration of interest: None.